FRI0191 Skin score in systemic sclerosis. (1st June 2001) - Sampaio-Barros, PD; Amstalden, EM; Samara, AM; Marques-Neto, JF
Abstract : Background: Objectives: To report the experience with the use of the Total Skin Score (TSS), in the original (OR-TSS) and modified (MR-TSS) Rodnan methods, in systemic sclerosis (SSc), analysing its clinical significance in the model of two (diffuse and limited) and three (diffuse, intermediate and limited) subgroups. Methods: Prospective study analysing skin thickness (assessed using the original and modified Rodnan TSS methods) in 56 patients with SSc. TSS results were compared with SSc clinical variants (divided in the model of two and three subgroups), pathological findings observed in standardised skin biopsies and cutaneous (calcinosis, telangiectasias, pigmentary abnormalities), systemic (articular, vascular, esophageal, pulmonary, cardiac, renal) and laboratory (antinuclear antibody, anticentromere antibody, anti-topoisomerase I antibody) manifestations. Data were analysed on the basis of whether patients had a low TSS (= < 20) or a high TSS (> 20), in both methods. Logistic regression analysis was performed to determine the independent variables that influenced TSS (in the two methods) and death (after a 5-year follow-up). Results: There was statistical association between TSS = < 20 and limited SSc (both methods, in the SSc model of two subgroups)), grade I skin biopsy (OR-TSS) and calcinosis (MR-TSS). The TSS > 20 was associated with diffuse SSc (in the SSc models of two and three subgroups), pigmentary abnormalities and articular involvement (both methods) and grade II and III skin biopsy (OR-TSS). There was a statistical trend between TSS = < 20 and calcinosis and anticentromere antibody (OR-TSS), as well as between TSS > 20 and pulmonary restrictive disease (MR-TSS) and anti-topoisomerase I antibody (OR-TSS). The multivariate logistic regression analysis indicated that the clinical variant was the most important factor that influenced significantly TSS (in both methods). In the SSc model of two subgroups, the diffuse variant was associated with TSS > 20 (both TSS methods) and pigmentary abnormalities, with a statistical trend related to pulmonary restrictive disease and anti-topoisomerase-I antibody, whereas the limited variant was associated with TSS = < 20, calcinosis and anticentromere antibody. In the SSc model of three subgroups, the diffuse variant was associated with TSS > 20 (both TSS methods) and pigmentary abnormalities, whereas the limited variant was associated with grade I skin biopsy; the intermediate variant was associated with calcinosis and telangiectasias. After a 5-year follow-up, there were 20 deaths (35.7%); the multivariate logistic regression analysis indicated that the vascular involvement influenced significantly death, despite the TSS score. Conclusion: TSS, in both original and modified Rodnan methods, represents an useful tool in the management of the skin involvement in SSc, permitting to differentiate distinct patterns in the clinical spectrum of the disease.